Morphometry of Liver Fluke (Fasciola Gigantica) Infecting Balinese Cattle - Oktaviana, Putu Anna; Suratma, Nyoman Adi; Wandia, I Nengah (Journal of Veterinary and Animal Sciences; Vol 2 No 1 (2019)DO - 10.24843/JVAS.2019.v02.i01.p02, 2019)
Fasciola hepatica and Fasciola gigantica belong to Trematoda family which can cause fasciolosis. Fasciola hepatica is commonly found in temperate climates, while Fasciola gigantica is found in areas with wet tropical climates. Research on Fasciola gigantica especially in Bali is still very little, was just limited to the prevalence, epidemiology and histopathology of liver. This study aims to determine the morphometry of Fasciola gigantica infecting Bali cattle in Bali. This descriptive study used 43 samples of worms. Measurement of morphometry is done by microscope equipped with camera Axio Cam ERc 5S and software used is IMAGEJ and ZEN LITE. The morphometric analysis showed that there were two differentiating factors that is PB (Body Length) and LB (Body Width). The morphometric of Fasciola gigantica in Bali is smaller compared to Fasciola gigantica in general but larger than Fasciola hepatica.